Kematangan Beragama dalam Perspektif Psikologi Tasawuf - Zulkarnain Zulkarnain; Farrel Damara (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The psychology of Sufism has a strong connection in all areas of human life in modern times. The modern human is not enough to be able to understand the material, scientific, technological and cultural needs. Certainly, modern humans demand answers on how to display spirituality in religious practices. Psychology and Sufism as a holistic approach oration that integrates psychic and spiritual can provide solutions to human problems. Through spirituality, a person will be able to purify the soul in religious behavior, improve morals, the reference lines in the noble values ​​of the religion he believes. Religious maturity contains patterns of adjustment with religious awareness and religious beliefs adopted. Applying the noble values ​​of religion that are embraced comprehensive in aspects of daily life. As a spiritual door (Sufism) is a container for the formation of a person's religious behavior carried out in religious activities. The purpose of this paper is to describe and certainly to know the maturity of religion from the perspective of Sufism psychology based on theorization. The psychology of Sufism is a typical paradigm to overcome the problem of human psychiatric illness through religious worship practices, healthy mental processes in life. Certainly able to find peace and happiness in living in diversity.